Long-term outcomes after catheter ablation of ventricular tachycardia in dilated vs. ischemic cardiomyopathy - Chakarov, Ivaylo; Müller, Julian; Ene, Elena; Berkovitz, Arthur; Sonne, Kai; Nentwich, Karin; Schupp, Tobias; Behnes, Michael; Deneke, Thomas (Journal of Clinical Medicine, 2022)
Ischemic (ICM) and dilated cardiomyopathy (DCM) represent the two main underlying heart diseases in patients referred for catheter ablation of ventricular tachycardia (VT). While VT ablation in ischemic cardiomyopathy is relatively well-studied, data in patients with DCM are still scarce. The study aimed to compare the acute and long-term outcomes in patients with ICM and DCM who underwent VT ablation at a high-volume center. Consecutive patients who underwent VT ablation from April 2018 to April 2021 were included retrospectively. Patients with ischemic cardiomyopathy were compared to those with dilated cardiomyopathy. The primary endpoint was rate of VT recurrences, the secondary endpoints included overall mortality, rehospitalization because of cardiac condition (VT, acute heart failure, acute myocardial infarction, heart transplantation or implantation of left ventricular assisting device), and major adverse cardiac events (MACE) at long-term follow-up. A total of 225 patients admitted for first VT ablation were included. A total of 156 patients (69%) revealed ICM and 69 (31%) DCM. After a mean follow-up of 22 months, the primary endpoint of VT recurrence occurred significantly more often in the patients with dilated cardiomyopathy (ICM n = 47; 37% vs. DCM n = 34; 64%; p = 0.001). In regard to the secondary endpoint of overall mortality, there was no difference between the two patient cohorts (DCM n = 9; 15% vs. ICM n = 22; 16%; p = 0.677); the patients with DCM showed significantly higher rehospitalization rates due to cardiac conditions (75% vs. 59%; p = 0.038) and more frequent MACE (68% vs. 52%; p= 0.036). In a Cox regression model, electrical storm at admission was shown to be a predictor for VT recurrence after successful catheter ablation (HR = 1.942: 95% CI 1.237-3.050; p = 0.004), while the ablation of every induced VT morphology during the procedure (HR = 0.522; 95% CI = 0.307-0.885; p = 0.016) contributed to a positive long-term outcome. DCM is associated with a higher risk of VT recurrence after catheter ablation compared to ICM. Furthermore, patients with DCM are more frequent re-hospitalized in the majority of cases due the VT recurrence. There is no difference in the long-term mortality between the two cohorts.